Role of Serum Fibrinogen Levels in Patients with Rotator Cuff Tears - Umile Giuseppe Longo (International Journal of Endocrinology, 2014)
Although rotator cuff (RC) tendinopathy is a frequent pathology of the shoulder, the real understanding of its aetiopathogenesis is still unclear. Several studies showed that RC tendinopathy is more frequent in patients with hyperglycemia, diabetes, obesity, or metabolic syndrome. This paper aims to evaluate the serum concentration of fibrinogen in patients with RC tears. Metabolic disorders have been related to high concentration of serum fibrinogen and the activity of fibrinogen has been proven to be crucial in the development of microvascular damage. Thus, it may produce progression of RC degeneration by reducing the vascular supply of tendons. We report the results of a cross-sectional frequency-matched case-control study comparing the serum concentration of fibrinogen of patients with RC tears with that of a control group of patients without history of RC tears who underwent arthroscopic meniscectomy. We choose to enrol in the control group patients with pathology of the lower limb with a likely mechanic, not metabolic, cause, different from tendon pathology. We found no statistically significant differences in serum concentration of fibrinogen when comparing patients with RC tears and patients who underwent arthroscopic meniscectomy (P = 0.5). Further studies are necessary to clarify the role of fibrinogen in RC disease.